Conceptual Bases of Formation Client-Oriented Organizational Culture of the High School - GULEI, Inna Aramovna; SMOLENSKAYA, Oksana Alekseevna; SHAVYRINA, Irina Valerievna; SHAPOVALOVA, Victoria Alexzandrovna (Journal of Advanced Research in Law and Economics; Vol 6 No 3 (2015): JARLE Volume VI, Issue 3(13), Winter 2015, 2017)
The article deals with urgent aspects of the formation and development of customer-oriented organizational culture of the high school. In terms of the position of the authors proposed a conceptual approach to the consideration of organizational culture as the primary vector of development of corporate management subsystems in high school, the value of the development trajectories of formation of organizational culture, and offers customer-oriented approach of formation of organizational culture of the university, which is based on a role model student as the central component of building corporate policy of the university. It is opened the essence of the concepts of customer-oriented, customer-oriented organizational culture of the university, is justified its multilevel structure. Customer orientation as a multilevel structure, according to the authors, reflects the relationships between objects internal and external environment of high school, their role in the process of selecting targets of client-oriented technologies and customer-level organizational culture of the university, showing the current level of technology and results. The authors propose a systematic approach to the formation of the organizational culture of the university, based on customer focus, technology, formation and development of the structural elements of the organizational culture, processes and modeling of social phenomena by means of cooperation and broadcast some of its elements in the general policy of the university. Settle conditions for the formation of customer focus as a method of effective development of high school to help improve rankings University in the educational environment, increase its competitiveness, development of scientific - research activities of the university at the international level